Evaluation of Supply Chain Management Effects on Consumer Preference for Cowpea Quality Features and Price Trend in Niger State - Onodugo Vincent A; Anowor Oluchukwu F; Ifediora Chuka; Aliyu Nasiru (International Journal of Supply Chain Management, 2019)
The concerns of dwindling food supply and over dependence on imported foods in Nigeria, especially in the face of dwindling foreign exchange, has prompted attention of experts on how to improve production and marketing of home-grown local food crops. The study assessed the quality characteristics and price preferences of consumers of Cowpea in the Niger State, Nigeria. The study adopted the survey design using quantitative research strategy. Primary data was collected from 600 famers over a 30-month period through the instrumentality of questionnaire. Hedonic price model was used to estimate the relationship between price and cowpea characteristics, and the Ordinary Least Square (OLS) analytical technique to investigate the impact of intrinsic characteristics on price in five varieties of cowpea. The regression analysis revealed that the respective value of R2 for Chanchaga markets is 0.72 and Bida markets is 0.77 which means that 72% and 77% of changes in the price of cowpea is explained by the changes in quality characteristics of cowpea in each market. The results indicated that consumer valued high protein content, sucrose content and dry matter content as the most important attributes as such they attracted higher prices. The study recommends among others that increase in protein content would make cowpea more attractive for the food industry and will have a positive impact on consumers’ nutritional health.